Borders, Centres and Peripheries in late Roman and Visigothic Iberia. (May 2015) - Wood, Jamie
<x content-type="archive" xml:space="preserve">Abstract</x> This article surveys scholarship on the evolving provincial organization of the Iberian Peninsula in the late and immediately post-Roman periods (fourth to early eighth centuries CE), when the region moved gradually from the control of the Western Roman Empire to that of the kingdom of the Visigoths, a "barbarian" group who had gradually integrated themselves into the late Roman order in the fourth and fifth centuries. My analysis of this issue over a long time frame suggests that the internal divisions and external boundaries of the late antique Iberian Peninsula (Roman Hispania) were highly fluid and liable to change in response to economic, military, religious and, above all, political factors. The exact make up of Hispania in this period was largely dependent on an ongoing dialogue – sometimes peaceful, sometimes conflictual – between central sources of authority, whether imperial or royal, and more regionally-based powers.